KINERJA KEUANGAN BERPENGARUH TERHADAP PENGUNGKAPAN TANGGUNGJAWAB SOSIAL PERUSAHAAN OTOMOTIF - Batohir, Hafid; Praptoyo, Sugeng (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
Corporate social responsibility is a transparent business practice which is based on ethical values which are performed by giving attention to the employees, community, and environment and it is designed to conserve the community in general and the stakeholders. The purpose of this research is to test the financial performance partially which is measured by using the sales growth, profit margin, return on asset, and return on equity to the disclosure of corporate social responsibility of automotive companies which are listed in Indonesia Stock Exchange, the data is the secondary data. The multiple linear regressions which are tested by using model feasibility test and t-test is used as the analysis technique. The instrument is the financial statement of the automotive companies which are listed in Indonesia Stock Exchange in 2009-2013 periods. The result of the research shows that the sales growth (PP), profit margin (PM), return on asset (ROA), and return on equity (ROE) have positive and significant influence to the disclosure and corporate social responsibility. It has been proven by the value of probability t test statistic with its value is under 0.05 (significance on Î± 5%).Keywords: Financial Performance, Disclosure and Corporate Social Responsibility.